Zachłanność autentyczności a wielokulturowość - Bakke, Monika (Er(r)go. Teoria - Literatura - Kultura, 2003)
Monika Bakke "Zachłanność autentyczności a wielokulturowość [The Greed for Authenticity and Multiculturalism]" Revolving around the artistic project by Marina Abramowic and Ulay, the article explores the issue of otherness and cultural translation of tradition